A novel use of Twitter to provide feedback and evaluations. (April 2014) - Desai, Bobby
Summary Background Inconsistencies in work schedules and faculty supervision are barriers to monthly emergency medicine (EM) resident doctor evaluations. Direct and contemporaneous feedback may be effective in providing specific details that determine a resident's evaluation. Objectives To determine whether Twitter, an easy to use application that is available on the Internet via smartphones and desktops, can provide direct and contemporaneous feedback that is easily accessible, and easy to store and refer back to. Methods First‐ to third‐year EM residents were administered a survey to assess their thoughts on the current monthly evaluation system. Subsequently, residents obtained a Twitter account and were instructed to follow a single general faculty Twitter account for ease of data collection. Following completion of an 8–week study period, a second survey was administered to assess resident thoughts on contemporaneous feedback and evaluations versus the traditional form. Results Of the 24 EM residents, 13 were available for study. A total of 220 'tweets' were provided by seven faculty members, with a mean of 11 tweets (range 8–17) per resident. The 13 residents received a total of eight formal evaluations from 19 faculty members. The second survey demonstrated that this method provided more detailed evaluations and increased the volume of feedback. Conclusion Contemporaneous feedback and evaluation provides a greater volume of feedback that is more detailed than end‐of‐course evaluations. Twitter is an effective and easy means to provide this feedback. Limitations included the length of study time and the inability to have all of the EM residents involved in the study.